Pediatric Eosinophilic Granuloma Associated With Delayed Epidural Hematoma Following on Seizure: A Case Report - Cho, Hyun Jeong; Park, Sung Chan; Lee, Jong Min; Jung, Na Young; Park, Jun Bum (Brain tumor research and treatment, 2024)
Eosinophilic granuloma (EG), a subtype of Langerhans cell histiocytosis (LCH), the monostotic form, is a rare condition characterized by a solitary bone lesion. It is even more unusual for this condition to be accompanied by an epidural hematoma (EDH). This case is unique in that it is the first to involve delayed EDH following a seizure. We describe a remarkable example of EG accompanied by an EDH and consider the rarity of this comorbidity. A 32-month-old boy developed a rapidly growing skull mass following a minor head injury. During surgical preparation for a biopsy, the patient experienced a single convulsion. Imaging following the seizure revealed an EDH in the vicinity of the mass. The mass was excised and confirmed to be an EG, but with positive margins. The patient underwent chemotherapy after systemic skeletal evaluation, in accordance with the LCH III protocol established by the Histiocytosis Society. EG is a rare neoplasm that typically presents as a painless growth on the skull that gradually enlarges over time. The correlation between EG and EDH is exceedingly uncommon, with only a few documented cases. This case study underscores the significance of considering EG in the differential diagnosis of an expanding cranium mass, even when associated with EDH. Prompt diagnosis and treatment can prevent serious complications and improve patient outcomes.